If it bleeds - King, Stephen (Hodder & Stoughton Ltd, 2021)
News people have a saying: 'If it bleeds, it leads'. And a bomb at Albert Macready Middle School is guaranteed to lead any bulletin. Holly Gibney of the Finders Keepers detective agency is working on the case of a missing dog - and on her own need to be more assertive - when she sees the footage on TV. But when she tunes in again, to the late-night report, she realises something is not quite right about the correspondent who was first on the scene. So begins 'If It Bleeds', a stand-alone sequel to the No. 1 bestselling THE OUTSIDER featuring the incomparable Holly on her first solo case - and also the riveting title story in Stephen King's brilliant new collection. Dancing alongside are three more wonderful long stories from this 'formidably versatile author' (The Sunday Times) - 'Mr Harrigan's Phone', 'The Life of Chuck' and 'Rat'. All four display the richness of King's storytelling with grace, humour, horror and breathtaking suspense. A fascinating Author's Note gives us a wonderful insight into the origin of each story and the writer's unparalleled imagination.